MANAGING SMALL BUSINESS ENTERPRISE: SOCIAL CAPITAL AND FINANCIAL APPROACH AT REGENCY PROBOLINGGO - Harmono, Harmono (Jurnal Keuangan dan Perbankan, 2009)
This study attempted to analyze management model of small business enterprise inProbolinggo regency. Conceptual framework was based on social capital and financial approach.Terms of finance would be analyzed with financial audit, and social capital consisting ofindividual behavior, organization behavior in groups, relationship with others and governmentinstitution which followed local social norms enhancing goals congruence. Research designintegrated both exploratory and confirmatory research. The unit of analysis was small businessenterprise, members of community organization Urban Poverty Project-2 in Probolinggoregency. The finding of research indicated four dimensions representing the managementmodel of small business enterprise. They were: 1) financial factor; 2) skill; 3) disciplines forquality; and 4) relationship factor. The next analysis was adjusted with demography cluster.Based on cluster and factors analysis it could be described that, groups in first cluster were 19%concerning in financial and relational factors. The second cluster was just 5% concerning toskill and discipline for quality. The third cluster consisted of 26% concerning to relational, andthe forth cluster was as the majority members, 50% of the population, concerning in financialand skill factors, and having significantly correlation between educations and income. Thisresult was appropriate to financial and institution audit.